2018
DOI: 10.1016/j.eja.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Canegro model for improved simulation of climate change impacts on sugarcane

Abstract: Crop models can be used for predicting climate change impacts and exploring adaptation strategies, but their suitability for such tasks needs to be assessed. Although the DSSAT-Canegro model has been used widely for climate impact studies, some shortcomings have been revealed. The objectives were to improve and evaluate the capability of DSSAT-Canegro to predict crop responses to climate change. Model changes included improved simulation of elevated temperature and atmospheric CO 2 concentration ([CO2]) impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
0
43
0
1
Order By: Relevance
“…While Tb can be changed in APSIM-Sugar software, such changes will affect all expansive growth processes. Tb for sprouting and tillering is clearly higher than for leaf appearance and elongation (Inman-Bamber, 1994;Singels and Smit, 2009) and this needs to be captured in future revisions of APSIM-Sugar for yield projections, especially under climate change (Jones and Singels, 2018;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While Tb can be changed in APSIM-Sugar software, such changes will affect all expansive growth processes. Tb for sprouting and tillering is clearly higher than for leaf appearance and elongation (Inman-Bamber, 1994;Singels and Smit, 2009) and this needs to be captured in future revisions of APSIM-Sugar for yield projections, especially under climate change (Jones and Singels, 2018;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Smit (2010) showed that for South African varieties grown in a glasshouse, the Tb for shoot emergence ranged between 16.8 and 18.1°C, much higher than the Tb adopted in APSIM-Sugar (9°C) and CANEGRO (10°C). The new version of CANEGRO now considers 16°C as Tb for this process (Jones and Singels, 2018). Tb cannot be varied for different processes of expansive growth in APSIM-Sugar.…”
Section: Default Settings With Variety Q117 and Par Interception Adeqmentioning
confidence: 99%
See 2 more Smart Citations
“…A utilização de modelos de simulação de culturas possibilita a individualização da influência de fatores ambientais e a determinação de parâmetros que governam a simulação de processos físicos e fisiológicos que compõem o crescimento e o desenvolvimento das plantas. No tocante à pesquisa científica, os modelos de simulação têm sido amplamente empregados para a comparação de manejos nutricionais, análise dos efeitos do déficit hídrico no rendimento das culturas, planejamento do uso da água, avaliação do efeito de alterações climáticas na produtividade das culturas, entre outras aplicações, tanto no Brasil, como no exterior (SCARPARE, 2011;SINGELS, 2018;RUAN et al;HU et al, 2019). Portanto, os modelos constituem uma ferramenta útil e indispensável, na medida em que o desempenho das culturas depende de interações complexas entre aspectos edáficos e condições meteorológicas, bem como de decisões sobre o seu manejo.…”
Section: Modelagem De Culturas: Importância E Históricounclassified